Strengthening Family Food Security through Socialization of Local Plant Cultivation as an Effort to Prevent Stunting in Dukun Village - Nessy Anggun; Selasih Putri; Bambang Budi; Indah Nur Widiyanti; Modesta Frila Lawalata (JURNAL PENGMAS KESTRA (JPK), 2026)
Nutrition issues in Indonesia remain a focus of government attention that requires serious handling from various sectors. Food security needs to be improved, one of which is through the cultivation of local crops that utilize yard space as an effort to prevent stunting. The objective of this Community Service activity was to provide information and education to mothers who are members of the Posyandu Balita (Child Health Center) in Dukun Village, Magelang Regency, on cultivating local crops as a means of reducing stunting in children. The community service method consisted of two sessions, namely providing educational material on cultivating local crops and practical training on cultivating local crops to support child nutrition. There were 21 participants in this activity, namely mothers who are cadres of the Toddler Health Center in Dukun Village, Magelang Regency, which was held in Dukun Village. The activity consisted of a pre-test, material delivery, followed by a question and answer session and practical training on local plant cultivation, and ended with a post-test and satisfaction survey. Based on the observations made, the participants were very enthusiastic, and the average post-test score increased compared to the pre-test score, from 94.28 to 98.09. This indicates that the participants understood the material on how to cultivate local plants well. The satisfaction survey results showed that 80% of the participants stated that they were very satisfied with the benefits of this community service program. Socialization and education activities such as this need to be continuously improved to increase the community's ability to cultivate local crops, which can be one of the efforts to prevent stunting.